Governing groundwater for NEXUS Gains: Solarizing irrigation, negotiating recharge, and including nature - Bruns, Bryan; Meinzen-Dick, Ruth S. (CGIAR, 2023)
Water stored in aquifers provides a crucial resource for people, crops, and ecosystems as it flows into springs, wetlands, streams, and rivers, and is lifted from wells. Rising demand for water, along with increasing droughts, floods, and heatwaves, all make groundwater more valuable.